Dynamic relationship between oil price volatility and stock market performance: an empirical analysis of the ASEAN-5 countries - Prabu, Darniya (2019)
This study examines the dynamic relationship between oil price volatility and stock market performance in the ASEAN-5 countries (Malaysia, Indonesia, Singapore, Thailand and Philippines). The study is extended to examine individual oil-exporting and oil-importing country’s reaction towards the volatility of oil prices. A balanced panel data is constructed for the five countries using monthly data from September 1999 to May 2018 where the WTI and Brent Crude oil prices were used as a proxy for world oil prices. The findings suggested that there exists a dynamic relationship between the volatility of WTI and Brent Crude oil prices and the stock market performance of the ASEAN-5 countries. The stock market returns of the oil-exporting countries are affected by the change in WTI prices whereas there is no relationship found between the stock market of the oil-importing countries and oil price volatility. These findings are supported by the stock valuation channel, fiscal channel and output channel which summarizes that there is a relationship between oil prices and stock market performance. By examining this linkage, some policy implications that can be utilised as guiding tools to the government and investors are provided.